Physicochemical characterisation of enzymatically hydrolysed derivatives of acetylated starch - Konował, Emilia; Lewandowicz, Grażyna; Le Thanh-Blicharz, Joanna; Prochaska, Krystyna (Carbohydrate polymers, 2012)
► Enzymatic hydrolysis of acetylated starch in membrane reactor. ► The influence of conditions of process on the surface-active properties of hydrolysates. ► Mixed adsorbed monolayer at the air/water interface for hydrocolloid–surfactant systems. ► Synergism in reducing the surface tension at the air/water interface. Potato starch modified to different degrees by substitution with acetyl groups was the subject of this study undertaken to determine the influence of conditions of enzymatic hydrolysis on the surface-active properties of hydrolysates of acetylated starch. The effect of acetylation of starch preparation on its susceptibility to enzymatic hydrolysis in the membrane reactor was also considered. All hydrolysates of acetylated starch samples investigated were found to bring a decrease in the surface/interfacial tension, both at the air/water and the toluene/water interfaces. For binary hydrolysate–surfactant systems, the surface mole fractions in the mixed adsorbed monolayer at the air/water interface were estimated. For mixed systems, the synergism in reducing the surface tension at the air/water interface was observed. The experimentally obtained dynamic surface tension data for the aqueous solution of acetylated starch hydrolysates were used to estimate the diffusion coefficients. Particle size distributions of the hydrolysates formed in the aqueous solutions were compared to those of commercial maltodextrin.